PEMATUHAN PRINSIP KERJASAMA ANTARA PELAKU PERCAKAPAN PADA NOVEL BERJUDUL “HARRY POTTER DAN BATU BERTUAH” - Ida Ayu Panuntun (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Cooperative  Principle  is  a  principle  which  used  to  become  an  effective  communication.  It  often appears in the conversation. Cooperative Principle  was proposed by Grice in 1975. It consists of four maxims in the conversation. Those are quantity maxim, quality maxim, relevance maxim and manner  maxim.  The  observance  of  the  four  maxims  used  in  order  to  gain  the  meaningful conversation. Novel entitled  “Harry Potter  dan Batu  Bertuah”  is one  of the  most popular novels. The conversations among the characters in that novel is interesting to be analyzed. The purposes of the study are to identify the maxims which observe the cooperative principle in term of meanings. The  method  used  in  this  study  was  descriptive  qualitative  with  cooperative  principle  analysis approach.  The  objects  of  the  study  were  43  conversations.  To  analyze  the  conversations  which observe the maxims are done by interpreting the meanings of the conversation. The findings of the conversations which observe the cooperative principle are as follow: 60.5% utterances observe the maxim of quantity; 16.3%  utterances observe the  maxim of relevance; 16.3%  utterances  observe the  maxim  of  manner  and  7%  utterances  observe  the  maxim  of  quality. The  finding  is  also suggested as a recommendation in the teaching learning process for the advanced learner level and the  senior  high  school  level. This  findings  can  be  applied  in  the  advanced  learner  level  in transferring  the  material  of  speaking.  Another  recommendation  is  suggested  for  the  senior  high school level in the English subject. It can be applied in the discussion of the material and question and answer session between the teacher and the students.Keywords: speech act, conversation, cooperative principle